Betamethasone Dipropionate Derivatization, Biotransformation, Molecular Docking, and ADME Analysis as Glucocorticoid Receptor. (6th July 2022) - Rashid, Sana; Anjum, Shazia; Ahmad, Aqeel; Nadeem, Raziya; Ahmed, Maqsood; Shah, Syed Adnan Ali; Abdullah, Muhammad; Zia, Komal; Ul-haq, Zaheer
Abstract : Betamethasone is an important glucocorticoids (GCs), frequently used to cure allergies (such as asthma and angioedema), Crohn's disease, skin diseases (such as dermatitis and psoriasis), systemic lupus erythematosus, rheumatic disorders, and leukemia. Present investigation deals to find potential agonist of glucocorticoid receptors after biotransformation of betamethasone dipropionate (1) and to carry out the molecular docking and ADME analyses. Biotransformation of 1 was carried out with Launaea capitata (dandy) roots and Musa acuminate (banana) leaves. M. acuminate furnished low-cost value-added products such as Sananone dipropionate (2) in 5% yields. Further, biocatalysis of Sananone dipropionate (2) with M. acuminate gave Sananone propionate (3) and Sananone (4) in 12% and 7% yields, respectively. However, Sananone (4) was obtained in 37% yields from Launaea capitata . Compound 5 was obtained in 11% yield after β -elimination of propionic acid at C-17 during oxidation of compound 1. The structure elucidation of new compounds 2-5 was accomplished through combined use of X-ray diffraction and NMR (1D and 2D) studies. In addition to this, molecular docking and ADME analyses of all transformed products of 1 were also done. Compounds 1-5 showed -12.53 to -10.11 kcal/mol potential binding affinity with glucocorticoid receptor (GR) and good ADME profile. Moreover, all the compounds showed good oral bioavailability with the octanol/water partition coefficient in the range of 2.23 to 3.65, which indicated that compounds 1-5 were in significant agreement with the given criteria to be considered as drug-like.